2022
DOI: 10.3389/fimmu.2022.834878
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Renal Risk Score and Histopathological Classification for Prediction of End-Stage Kidney Disease and Factors Associated With Change in eGFR After ANCA-Glomerulonephritis Diagnosis

Abstract: IntroductionThe “Renal Risk Score” (RRS) and the histopathological classification have been proposed to predict the risk of end-stage kidney disease (ESKD) in ANCA-associated glomerulonephritis (ANCA-GN). Besides, factors associated with kidney function recovery after ANCA-GN onset remain to be more extensively studied. In the present study, we analyzed the value of the RRS and of the histopathological classification for ESKD prediction. Next, we analyzed factors associated with eGFR change within the first 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The average follow-up time of our study (38.99 months) was similar with that of Brix's study (34 months), but the average follow-up time was shorter in Luo's study (14.3 months) (28). Till now, some reports have evaluated the prognostic value of Berden's classification and RRS, and found that RRS showed better discrimination than Berden's classification for predicting overall renal survival (13,29). However, these studies only evaluated predictive value in terms of discrimination ability and compared predictive ability for overall renal survival.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The average follow-up time of our study (38.99 months) was similar with that of Brix's study (34 months), but the average follow-up time was shorter in Luo's study (14.3 months) (28). Till now, some reports have evaluated the prognostic value of Berden's classification and RRS, and found that RRS showed better discrimination than Berden's classification for predicting overall renal survival (13,29). However, these studies only evaluated predictive value in terms of discrimination ability and compared predictive ability for overall renal survival.…”
Section: Discussionsupporting
confidence: 83%
“…Since the publication of Berden's classification, its predictive value for renal survival has been verified in many studies. Among the four groups of Berden's classification, the patients in the sclerotic group had the worst prognosis and those in the focal group had the best prognosis (13). Different from the focal and sclerotic groups, there was a controversy about renal outcomes of the crescentic and mixed groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a research including Japanese adults showed that there was no significant difference between the ARRS and conventional prognostic tools prognostic ability. 14 However, Brilland et al 33 found that the ARRS has a better predictive value for ESKD than the Berden classification. Current study was the first to compare predictive value of ARRS, Berden classification, and RPGN in children with AAGN.…”
Section: Discussionmentioning
confidence: 99%
“…24 The ARRS was found to have excellent discrimination, and since its publication, multiple retrospective cohort studies have been performed on cumulatively over 2000 patients across three continents. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] It was recently incorporated into a proposed tool to identify patients who may benefit from plasma exchange after the results of the plasma exchange and glucocorticoid dosing in the treatment of anti-neutrophil cytoplasm antibody-associated vasculitis trial. 40,41 A recent meta-analysis of 11 ARRS validations with a median number of 130 patients per study (range, 37-252) highlighted the need for larger-scale studies.…”
Section: Introductionmentioning
confidence: 99%